Pengaruh Nilai Kerja Islami dan Budaya Kerja Islami Terhadap Produktivitas Kerja BSI - Luh Ratih; Kurniawati Kurniawati; Sahrial Sahrial (Nirta Learning Centre, 2023)
The purpose of the study was to determine the effect of Islamic work values on work productivity of BSI Denpasar Branch employees, to determine the effect of Islamic work values on work productivity of BSI Denpasar Branch employees, to determine the effect of Islamic work values and culture simultaneously on work productivity. This research uses quantitative research, with questionnaire data collection techniques. This study uses validity and reliability test analysis techniques, multiple regression testing using the SPSS 26 program. The results obtained that the coefficient value of the X1 variable Islamic work value is 0.428 with a significance value of 0.037 <0.05 while the coefficient value of the X2 variable Islamic work culture is 0.425. with a significance value of 0.034 <0.05. These results indicate that there is an influence between Islamic work values and Islamic work culture on employee work productivity either partially or simultaneously.